2017
DOI: 10.1002/bmc.3999
|View full text |Cite
|
Sign up to set email alerts
|

Identification of differential metabolic characteristics between tumor and normal tissue from colorectal cancer patients by gas chromatography–mass spectrometry

Abstract: Colorectal cancer (CRC) is one of the most common human malignancies and encompasses cancers of the colon and rectum. Although the gold-standard colonoscopy screening method is effective in detecting CRC, this method is invasive and can result in severe complications for patients. The purpose of this study was to determine differences in metabolites between CRC and matched adjacent nontumor tissues from CRC patients, to identify potential biomarkers that may be informative and developed screening methods. Meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 31 publications
3
10
0
Order By: Relevance
“…28 The correlations between high catecholamine levels and stress, as well as the occurrence and development of tumors, have also received increasing attention. In related research of CRC tissue at an early stage, we found that the contents of tyrosine and 5-oxoproline were also significantly higher compared with the control group, 16 which is consistent with the current results of urine analysis (Figure 5). However, this change has not been found in other CRC studies.…”
Section: Upregulation Of Amino Acid Metabolismsupporting
confidence: 90%
See 3 more Smart Citations
“…28 The correlations between high catecholamine levels and stress, as well as the occurrence and development of tumors, have also received increasing attention. In related research of CRC tissue at an early stage, we found that the contents of tyrosine and 5-oxoproline were also significantly higher compared with the control group, 16 which is consistent with the current results of urine analysis (Figure 5). However, this change has not been found in other CRC studies.…”
Section: Upregulation Of Amino Acid Metabolismsupporting
confidence: 90%
“…Therefore, it is a typical feature of CRC, and glycolysis is more active than oxidative phosphorylation even under normoxic conditions. 31,32 That is, glucose uptake by cancer increases, and the glucose content in normal tissues decreases; this was confirmed by our previous analysis of CRC tissue samples 16 and other researchers. 33 Our present study revealed that urinary concentrations of glucose, glucuronic acid, and threonic acid were significantly higher in patients with CRC than in healthy controls (Figure 4).…”
Section: Upregulation Of Glycolysissupporting
confidence: 82%
See 2 more Smart Citations
“…There are many reports describing dynamic reprogramming of metabolic pathways in CRC 12,13 . The protooncogene MYC regulates various metabolic pathways in CRC, including the glycolysis 14 and tryptophan pathways 15 .…”
mentioning
confidence: 99%